2022
DOI: 10.3389/fmicb.2022.815622
|View full text |Cite
|
Sign up to set email alerts
|

A C∧S-Cyclometallated Gold(III) Complex as a Novel Antibacterial Candidate Against Drug-Resistant Bacteria

Abstract: The worldwide emergence and spread of infections caused by multidrug-resistant bacteria endangers the efficacy of current antibiotics in the clinical setting. The lack of new antibiotics in the pipeline points to the need of developing new strategies. Recently, gold-based drugs are being repurposed for antibacterial applications. Among them, gold(III) complexes have received increasing attention as metal-based anticancer agents. However, reports on their antibacterial activity are scarce due to stability issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 84 publications
6
16
1
Order By: Relevance
“…Previous studies on the antimicrobial activity of analogous gold(I) and gold(III) complexes showed a broad spectrum of antibacterial activities, and some even had a certain degree of selectivity towards Gram-positive species [ 27 ]. This trend is similar to that observed among clinical bacterial strains using the gold(III) complex 1 , presenting the lowest MIC values (8–16 mg/L) among the Gram-positive strains in contrast to Gram-negative strains (64 mg/L) [ 21 ]. Taking into account that Staphylococcus spp.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Previous studies on the antimicrobial activity of analogous gold(I) and gold(III) complexes showed a broad spectrum of antibacterial activities, and some even had a certain degree of selectivity towards Gram-positive species [ 27 ]. This trend is similar to that observed among clinical bacterial strains using the gold(III) complex 1 , presenting the lowest MIC values (8–16 mg/L) among the Gram-positive strains in contrast to Gram-negative strains (64 mg/L) [ 21 ]. Taking into account that Staphylococcus spp.…”
Section: Discussionsupporting
confidence: 85%
“…It should be noted that gold(III) dithiocarbamate complexes were more active against Gram-positive strains than the comparative antibiotics, ampicillin (except in the case of S. xylosus ) and vancomycin (VAN). In the case of Gram-negative species, and similar to what was observed with human strains [ 21 ], 1 did not show antibacterial activity, observing MIC values equal to 64 mg/L. Among the gold(III) complexes studied, 2f was the most active with MICs of 4–8 mg/L from all Gram-negative species including P. aeruginosa .…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Accordingly, the biodistribution of gold antibiotics may be improved by inclusion in cyclodextrins ( Morgen et al, 2019 ; Tomasello et al, 2021 ). Recent studies have also described a potent synergistic microbicidal effect with antibiotics, suggesting that gold compounds may have great application prospects in combination therapy, potentiating the efficacy of clinically used antibiotics ( Ratia et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%